SUDDEN DEATH OF MIDDLE AGED MALE DUE TO CARDIAC TAMPONADE (Journal of Forensic Medicine & Toxicology, 2015)
The “tamponade “ is a French word meaning “ to stop”, that is the closure or blockage of a wound or body cavity as if by a tampon especially to stop bleeding. The cardiac tamponade also known as pericardial tamponade, is an acute type of pericardial effusion in which fluid, pus, blood, clots or gas accumulates in the pericardium, resulting in slow or rapid compression of the heart leading on to the stoppage of heart functions. This commonly occurs as a result of chest trauma( both blunt and penetrating), but can also be caused by myocardial rupture. Myocardial rupture is a some what uncommon cause of pericardial tamponade and is more likely to happen in elderly individual. These deaths are vary rare and unusual in adults and middle aged individuals. We present a case of sudden death of a middle aged male person due to cardiac tamponade consequent to myocardial rupture secondary recent and old attacks of myocardial infarctions while executing his routine office work. It emphasizes on meticulous examination of vital organs like heart in cases of sudden deaths.
Keywords: Myocardial rupture; pericardial effusion; sudden death; tamponade